Study The Some Aspects of The Immune Response For Pregnant Women Infected with T.Gondii and Determine The Genotyping of This Parasite - Hashim A. Abdulameer; Hashim R. Tarish; Alaa J. Hassan (Kufa Journal for Nursing Sciences)
Objectives: This study aims to find out the immune response (antibodies and cytokines) for women with disease T.Gondii and correlation between them calibrated and the effects on the patients of the difference age groups.